Frequency of Tinnitus with Hearing Loss in Old Age Group - Iftikhar, Huda (Indus Journal of Bioscience Research, 2025)
Objectives: determine frequency of Tinnitus in older age group patients presenting with hearing loss. Study Settings: Department of ENT, Madinah Teaching Hospital, Faisalabad. Duration of Study: Data Collection: A cross-sectional study was conducted on 95 patients aged 60–85 years with hearing loss. Participants were selected using a non-probability consecutive sampling technique. Tinnitus was diagnosed based on clinical evaluation, including otoscopic examination, tympanometry, and pure-tone audiometry. Demographic and clinical data were collected and analyzed using SPSS version 25.0. Results: The prevalence of tinnitus was 58.9%. Tinnitus was more common in rural residents (69.6%, p = 0.011) compared to urban residents. Gender-wise, tinnitus was higher in males (66.7%) than females (52.0%, p = 0.147). The prevalence varied with education levels but was highest among those with primary education (71.4%, p = 0.165). No significant associations were found with age (p = 0.477) or socioeconomic status (p = 0.155). Conclusion: Tinnitus is a prevalent condition among older adults with hearing loss in Pakistan, with a significant association with rural residence. Addressing modifiable risk factors, improving access to audiological services, and incorporating public health campaigns can reduce the burden of tinnitus and improve quality of life for affected individuals.